2009
DOI: 10.1016/j.gene.2008.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and promoter use in TFII-I genes

Abstract: TFII-I proteins are ubiquitously expressed transcriptional factors involved in both basal transcription and signal transduction activation or repression. TFII-I proteins are detected as early as at two-cell stage and exhibit distinct and dynamic expression patterns in developing embryos as well as mark regional variation in the adult mouse brain. Analysis of atypical small and rare chromosomal deletions at 7q11.23 points to TFII-I genes (GTF2I and GTF2IRD1) as the prime candidates responsible for craniofacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Despite the absence of novel mutations in the small number of individuals tested, the association results presented herein remain strongly suggestive that GTF2i plays a role in the etiology of ASDs, particularly in those individuals with severe social skills problems and high levels of repetitive behaviors. GTF2i is subject to alternative splicing, which generates isoforms that show different activities and play distinct biological roles (Makeyev and Bayarsaihan 2009;Hakre et al 2006). The particular risk haplotype could be linked to other polymorphisms or mutations associated with differential splicing of the gene, resulting in abnormal expression or function of GTF2i protein which may be associated with autism vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the absence of novel mutations in the small number of individuals tested, the association results presented herein remain strongly suggestive that GTF2i plays a role in the etiology of ASDs, particularly in those individuals with severe social skills problems and high levels of repetitive behaviors. GTF2i is subject to alternative splicing, which generates isoforms that show different activities and play distinct biological roles (Makeyev and Bayarsaihan 2009;Hakre et al 2006). The particular risk haplotype could be linked to other polymorphisms or mutations associated with differential splicing of the gene, resulting in abnormal expression or function of GTF2i protein which may be associated with autism vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is unlikely as transcription of Gtf2ird1 in the (Tg(Alb1-Myc)166.8) mutants was undetectable (24), and analysis of the mutant transcript produced in the Gtf2ird1 tm1Hrd mice reported here indicate very low levels of protein synthesis. All of the reported splice isoforms and (putative) alternative promoter-driven transcripts (18,27) include exons 2 and 3, and would, therefore, be subject to the same translation constraints as the 3␣7 isoform used in the above analysis. Therefore, our estimate of 6% total protein synthesis in homozygous Gtf2ird1 tm1Hrd mice applies, regardless of alternative splicing possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to imagine how such a small amount of residual protein is sufficient to explain these significant phenotypic differences. Furthermore, the exon 1 alternatives 1a and 1b (27), and the much more frequently used exon 1, all cluster together within the same 1-kb region of the genome, which would suggest that all transcripts fall under the same regulatory constraints, even if there is some wobble around the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
“…TFII-I ( GTF2I in humans and Gtf2i in mice) belongs to a family of vertebrate-specific transcription factors, encoded by three related genes that are closely located in human chromosome 7 (Fig 1A, ref 9). Genetic ablation studies in mice demonstrated that it is an essential gene as ablation causes early embryonic lethality with severe defects in angiogenesis and vasculogenesis most likely due to deregulation in the vascular endothelial growth factor receptor-2, VEGFR2 gene (10).…”
Section: Biochemical Properties and Structural Features Of Tfii-imentioning
confidence: 99%
“…The best characterized is TFII-I, which has at least four alternatively spliced isoforms in humans (α, β, γ and Δ) (9, 14). However, the expressions patterns or transcriptional functions of the beta, gamma and delta isoforms are currently unknown (9). The Δ and β-isoforms were shown to have opposing transcription functions in NIH 3T3 cells (15).…”
Section: Biochemical Properties and Structural Features Of Tfii-imentioning
confidence: 99%